PROSES PEMBUATAN HEADING PC-BAR MENGGUNAKAN MESIN HEADING PANAS DI PT WIJAYA KARYA BETON TBK PPB MAJALENGKA - Febriyanto, Muhammad Rival; Koswara, Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
This Practical Work Report explains the process of making PC Bar heading using a hot heading machine and the quality control process of PC Bar head quality at PT. Wijaya Karya Beton Tbk PPb Majalengka. The goal is to make PC Bar heads using hot heading machines and carry out quality control of PC Bar quality. In making PC Bar headings using hot heading machines, there are several stages from air supply, oil supply, workpiece clamping, workpiece heating, hammer forming, workpiece removal and cooling. In addition, this report discusses the quality control process of PC Bar head quality. PC-Bar headings that pass the Engineering and Quality process have a head diameter of 13-14 mm and a head thickness of 5-6 mm. Through this practical work report, it is hoped that readers can gain insight into the process of making PC Bar heads using hot heading machines and the company's contribution in maintaining product quality.